2019
DOI: 10.1039/c9cp03812d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the deep-sea osmolyte TMAO on the temperature and pressure dependent structure and phase behavior of lipid membranes

Abstract: The deep-sea osmolyte TMAO does not only stabilize proteins against high pressure, it affects also the fluidity and lateral organization of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 47 publications
12
59
0
Order By: Relevance
“…Membranes are complex structures, 29 consisting of many different lipids, and organisms are able to adapt the properties of their cytoplasmic membranes in response to changes in the environment by changing the lipid composition. [5][6][7][30][31][32][33][34][35][36][37][38][39][40] Bacterial and eukaryal lipids are mainly composed of two acyl chains, which are bound via an ester linkage to glycerol. These lipids are organized in a bilayer such that the polar head-groups stick into the water phases while the carbon chains are directed towards the inner side of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Membranes are complex structures, 29 consisting of many different lipids, and organisms are able to adapt the properties of their cytoplasmic membranes in response to changes in the environment by changing the lipid composition. [5][6][7][30][31][32][33][34][35][36][37][38][39][40] Bacterial and eukaryal lipids are mainly composed of two acyl chains, which are bound via an ester linkage to glycerol. These lipids are organized in a bilayer such that the polar head-groups stick into the water phases while the carbon chains are directed towards the inner side of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing osmolytes, such as trimethylamine oxide (TMAO), glutamate, betaine, alanine, β‐hydroxybutyrate (β‐HB), mannosylglycerate, di‐myo‐inositol phosphate and N‐Acetyl‐β‐lysine, are present in high concentrations in many piezophilic organisms . These molecules were shown to increase protein stability (see, eg, References ) and this increase in stability is not accompanied by volume changes . Such increase in stability may have a physiological role in piezophiles.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in pressure will lead to changes in the structures and sizes of these domains as well as in the functional state of the membrane. The low pressures can change the local composition of biological membrane lipid domains, which have significant biochemical implications (86). In general, the maintenance of basic physiological functions of biological membranes requires the dynamic and structural properties of cell membranes.…”
Section: Effects Of High Hydrostatic Pressure On Proteinmentioning
confidence: 99%
“…In general, the maintenance of basic physiological functions of biological membranes requires the dynamic and structural properties of cell membranes. Manisegaran et al reported that HHP and low temperature have a strong influence on lipid biological membranes, mainly because they both affect the fluidity of biological membranes to a large extent, leading to tight packing and limiting acyl-chain movement (86).…”
Section: Effects Of High Hydrostatic Pressure On Proteinmentioning
confidence: 99%
See 1 more Smart Citation